Habitat filtering not dispersal limitation shapes oceanic island floras: species assembly of the Galápagos archipelago. (10th March 2017) - Carvajal‐Endara, Sofía; Hendry, Andrew P.; Emery, Nancy C.; Davies, T. Jonathan
Abstract: Remote locations, such as oceanic islands, typically harbour relatively few species, some of which go on to generate endemic radiations. Species colonising these locations tend to be a non‐random subset from source communities, which is thought to reflect dispersal limitation. However, non‐random colonisation could also result from habitat filtering, whereby only a few continental species can become established. We evaluate the imprints of these processes on the Galápagos flora by analysing a comprehensive regional phylogeny for ~ 39 000 species alongside information on dispersal strategies and climatic suitability. We found that habitat filtering was more important than dispersal limitation in determining species composition. This finding may help explain why adaptive radiation is common on oceanic archipelagoes – because colonising species can be relatively poor dispersers with specific niche requirements. We suggest that the standard assumption that plant communities in remote locations are primarily shaped by dispersal limitation deserves reconsideration.